2009
DOI: 10.1007/s12253-009-9211-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vascular Endothelial Growth Factors A, C and D in Human Breast Tumors

Abstract: Available evidence suggests that vascular endothelial growth factor (VEGF) a potent regulator of vasculogenesis and tumor angiogenesis may be a predictor of recurrence in breast cancer patients. We sought to determine whether VEGF serum levels (VEGF-A, VEGF-C and VEGF-D) in 377 patients with malignant and benign breast tumors differ and whether there is association between vascular growth factors, clinicopathologic features and prognosis. There was no significant difference in investigated circulating angiogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 20 publications
4
13
0
2
Order By: Relevance
“…The COX analysis showed that the sVEGF-C level might be an independent risk factor of the outcome for GBC. These findings were consistent with those reports showing that a high sVEGF-C level was related to poor prognosis in patients with breast tumors [ 25 ] and gastric cancer [ 10 ]. Other studies have reported that overexpression of VEGF-C was correlated with a poor outcome in GBC patients [ 18 ] and that the serum VEGF-D level in PTC patients might be a useful marker for predicting the outcome [ 11 ].…”
Section: Discussionsupporting
confidence: 93%
“…The COX analysis showed that the sVEGF-C level might be an independent risk factor of the outcome for GBC. These findings were consistent with those reports showing that a high sVEGF-C level was related to poor prognosis in patients with breast tumors [ 25 ] and gastric cancer [ 10 ]. Other studies have reported that overexpression of VEGF-C was correlated with a poor outcome in GBC patients [ 18 ] and that the serum VEGF-D level in PTC patients might be a useful marker for predicting the outcome [ 11 ].…”
Section: Discussionsupporting
confidence: 93%
“…The correlation between VEGF-A and VEGF-D was also observed in canine and human mammary tumors. 8,16 Moreover, a correlation between VEGF-D and VEGFR-3 was found in the IC model, which might be related to its lymphangiogenic properties as it was also observed in IMC 8 and IBC. 53 It seems that angiogenic and lymphangiogenic processes are related in CC while the lymphangiogenic process dominates in IC.…”
Section: Discussionsupporting
confidence: 54%
“…Our study expands upon these findings by demonstrating differences in the platelet cytokine repertoire between hosts bearing specific luminal breast tumors and cancer-free hosts, and establishing that platelets continue to promote cancer progression even after tumor cells have disseminated to distant sites. Indeed, platelets provide a major serum source of many pro-angiogenic proteins in the circulation of patients with breast (38) and colorectal cancer (39). Hence, our finding that both patelet cargo and function are quantitatively different in hosts bearing certain luminal breast cancers than they are in cancer-free individuals serves as a prerequisite for analyzing platelets from breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%